ANALISIS MUTU BISKUIT MORINGNA SEBAGAI ALTERNATIF ANEMIA PADA REMAJA PUTRI - Aulya Pratiwi; Mona Fitria; Agus Sulaeman; Fred Agung; Yenny Moviana (Jurnal Gizi dan Dietetik, 2023)
The main cause of iron nutritional anemia in women is the lack of dietary iron (Fe) intake. Iron intake can be obtained from foods such as biscuits. Moringa flour and mung bean flour added as biscuit ingredients can be used as a high-iron snack in an effort to increase iron intake in adolescent girls. This study aims to determine the effect of the formulation of Moringa flour and mung bean flour on organoleptic properties and iron content. This research is an experimental study with a formulation ratio of F1 75%: 25%, F2 50%: 50% and F3 25%: 75%. The organoleptic test was carried out by 30 moderately trained people, then the best results were tested for iron levels by the ICP-OES (Inductively Coupled Plasma-Optical Emission Spectrometry) method. Data analysis used the Kruskal Wallis test, followed by the Mann Whitney test method. The biscuit that has the highest score is the F1 formulation with a ratio of moringa flour and mung bean flour 75%: 25%. One serving is 60 grams and can meet 24% of iron needs. The results of the statistical test found a value (p (0.000) < (0.05)) which means that there is an effect of the formulation of Moringa flour and mung bean flour on the taste of biscuits, and there is an effect on aspects of taste, aroma, and texture of biscuits. This research can be continued by improving the texture of the product to further increase its acceptability and conducting research on the target.